Clinical investigation of mucosal thickness stability after soft tissue grafting around implants: A 3-year retrospective study - Speroni Stefano; Cicciù Marco; Maridati Paolo; Grossi Giovanni; Maiorana Carlo (Wolters Kluwer Medknow Publications, 2010)
Purpose: To assess the long-term stability of gingival grafts placed around dental implants at the time of second surgery uncovering and to further investigate the association between mucosal thickness (MTh) by demographic variables and clinical investigation. Materials and Methods: Fourteen patients with submerged dental implants covered by inadequate keratinized mucosa were studied. The subjects underwent a periimplant plastic surgery (PPS) at the second-stage dental implant surgery and free gingival autograft orsubepithelial connective tissue graft were used according to the patients′ clinical situation. Clinical measurement of MTh was assessed by bone sounding with a periodontal probe using customized acrylic stents andthe values were recorded at baseline (day of graft) and at 0.5, 1.5, 4, 12, 24 and 36 months after grafting. Results: At 12 months postoperatively, the mean MTh was 2.89 mm, with a mean additional increase of 1.75 mm when compared with baseline (P=0.0001). No statistically significant differences in MTh were found between the 12- and the 36-month observations (P=0.09). In addition, at 36 months, a thin mucosa was associated with a greater increase in the MTh compared with a thick mucosa (2.14 and 0.64 mm, respectively, P=0.006). Similarly, the mandibular sites were associated with a greater increase in the MTh in comparison with the maxillary sites (2.17 and 0.81 mm, respectively; P=0.02). Conclusions: Within the limitations of this investigation, the data suggest that PPS at the second-stage dental implant surgery could results in additional increases in MTh, especially when it is performed in areas where the mucosa is of a thin biotype.